A Review on Recent Arabic Information Retrieval Techniques - AARAB, Abdelkrim; Oussous , Ahmed; Saddoune, Mohammed (EAI Endorsed Transactions on Internet of Things, 2022)
Information retrieval is an important field that aims to provide a relevant document to a user information need, expressed through a query. Arabic is a challenging language that gained much attention recently in the information retrieval domain. To overcome the problems related to its complexity, many studies and techniques have been presented, most of them were conducted to solve the stemming problem. This paper presents an overview of the Arabic information retrieval process, including various text processing techniques, ranking approaches, evaluation measures, and some important information retrieval models. The paper finally presents some recent related studies and approaches in different Arabic information retrieval fields.